2022
DOI: 10.3390/rs14143336
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Characteristics during the COVID-19 Lockdown in China: Optical Properties, Vertical Distribution, and Potential Source

Abstract: The concentration changes of aerosols have attracted wide-ranging attention during the COVID-19 lockdown (CLD) period, but the studies involving aerosol optical properties (AOPs) are relatively insufficient, mainly AOD (fine-mode AOD (AODf) and coarse-mode AOD (AODc)), aerosol absorption optical depth (AAOD), and aerosol extinction coefficient (AEC). Here, the remote-sensing observations, Modern-Era Retrospective analysis for Research and Applications, Version 2 (MERRA-2) products, backward-trajectory, and pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
2
1
0
Order By: Relevance
“…It also indicates that pollution control policies may not have led to a reduction in anthropogenic aerosols (e.g., raw coal use) in some regions. This is consistent with the findings of Jin et al [74].…”
Section: Effects Of Chinese Pollution Control Policies On the Aerosol...supporting
confidence: 94%
See 1 more Smart Citation
“…It also indicates that pollution control policies may not have led to a reduction in anthropogenic aerosols (e.g., raw coal use) in some regions. This is consistent with the findings of Jin et al [74].…”
Section: Effects Of Chinese Pollution Control Policies On the Aerosol...supporting
confidence: 94%
“…It also indicates that pollution control policies may not have led to a reduction in anthropogenic aerosols (e.g., raw coal use) in some regions. This is consistent with the findings of Jin et al [74]. We found that the annual-average variation of OF of different types of aerosols in different regions since the implementation of the pollution control policy is not obvious (Figure 10).…”
Section: Effects Of Chinese Pollution Control Policies On the Aerosol...supporting
confidence: 93%
“…Using LiDAR data, Nicolae et al [31] reported that the proportion of small particles of the total particles had increased in the upper troposphere but remained almost constant in the low troposphere over Romania. Using MODIS and Cloud-Aerosol LiDAR and Infrared Pathfinder Satellite (CALIPSO) data, Jin et al [32] observed a reduction in AOD and near-surface aerosol extinction coefficient (<2 km) in most areas of China during lockdown period compared to pre-lockdown period.…”
Section: Introductionmentioning
confidence: 99%